Peranan Pesantren Dr. Syekh Salman Daim terhadap Perkembangan Islam di Desa Bandar Rejo Kecamatan Bandar Masilam Kabupaten Simalungun - Fahmi, Muhammad (TSAQOFAH, 2024)
This study entitled The Role of Dr. Islamic Boarding Schools. Sheikh Salman Daim on the Development of Islam in Bandar Rejo Village, Bandar Masilam District, Simalungun Regency. The formulation of the problem in this study is how is the biography of Dr. Syekh Salman Daim as the founder of the Islamic boarding school, what is the history of the establishment of the Dr. Sheikh Salman Daim and what is the role of Dr. Salman Daim in the development of Islam in Bandar Rejo Village. The purpose of this study is to find out how the biography of Dr. Syekh Salman Daim as the founder of the Islamic boarding school, to find out the history of the establishment of the Dr. Sheikh Salman Daim, and to find out the role of Dr. Sheikh Salman Daim in the development of Islam in Bandar Rejo Village. The benefit of this research is for the reader after reading this research it is hoped that the reader will gain new knowledge about the role of Islamic boarding schools in the development of Islam in the vicinity of the pesantren location, this research is expected to provide new references for students and other academics, it is hoped that this research can become material for government consideration paying attention to Islamic boarding schools which before this country's independence were the biggest bastion against colonial occupation. The method used in this research is descriptive qualitative method because this method is considered very appropriate so that the writer can describe various sources of data and information in the field. The result of this research is Dr. Syekh Salman Daim is a scholar who was born on January 1, 1942 in Sipare-pare Village, who is the son of a farmer who studied tareqat until he occupied the 36th lineage of the Thariqat Naqsyabandiyah Al-Kholidiyah Jalaliyah, he founded the Dr. Islamic boarding school. Sheikh Salman Daim, who was originally only a place of encouragement for the congregation of the Naqsyabandiyah tariqat under the leadership of Sheikh Salman Da'im. Dr. Syekh Salman Daim is a scholar who holds the 36th genealogy of the Thariqat Naqsyabandiyah Al-Kholidiyah Jalaliyah, who continues to practice his knowledge so as to make tareqat places which gradually develop into Islamic boarding schools and where initially many people who did not become congregations of tareqat gradually became congregations tareqat. And boarding school Dr. Syekh Salman Daim contributed in the field of education for Badar Rejo Village.